Kinetics of prostaglandin production in various inflammatory lesions, measured in draining lymph. - Johnston, M. G. (1979)
Efferent lymph was collected over long periods via catheters surgically placed in popliteal and prefemoral lymph nodes of sheep. Prostaglandin (PG) E and F equivalents were measured with a radioimmunoassay. After stimulation with heat-killed Escherichia coli, PG levels rose dramatically in the efferent lymph but were undetectable in the contralateral control lymphatics or in the systemic circulation. When E coli were infused directly into a lymph node, the PG levels in the effluent lymph were inhibited with indomethacin. Carrageenan, delayed hypersensitivity, and lymphocyte transfer reactions were also studied. In the classic acute inflammations (caused by E coli and carrageenan) the PG levels rose early in the response (first 4 to 6 hours) compared with delayed production in the immune reactions. With PPD, PG levels peaked between 10 and 20 hours after injections, while PG rose 127 hours after allogeneic lymphocytes were injected. These results are discussed in relation to the role of PG in inflammation, and the use of the sheep lymphatic model in PG research is emphasized.